Hydrothermal Synthesis of Platinum‐Group‐Metal‐Free Catalysts: Structural Elucidation and Oxygen Reduction Catalysis. Issue 14 (7th December 2017) - Gokhale, Rohan; Tsui, Lok‐Kun; Roach, Kristin; Chen, Yechuan; Hossen, Md Mosaddek; Artyushkova, Kateryna; Garzon, Fernando; Atanassov, Plamen
Abstract: A hydrothermal approach to generate a platinum‐group‐metal‐free (PGM‐free) Fe−N−C catalyst for the oxygen reduction reaction (ORR) is introduced. The process involves partial carbonization by hydrothermal means followed by thermal treatment to obtain the final catalysts. Detailed X‐ray scattering analysis of the glucose−imidazole catalysts (termed as GLU‐IMID‐C catalysts), obtained for the first time with the use of CarbonXS GUI program, reveals the presence of face‐centered cubic (FCC) iron nanoparticles embedded in partially graphitic carbon in all catalyst variations. We also report the physical characterization of these catalysts by using X‐ray photoelectron spectroscopy, Brunauer−Emmett−Teller surface area analysis, and transmission electron microscopy. The electrocatalytic behavior of the catalysts towards oxygen reduction is studied separately in acidic and alkaline electrolytes by rotating ring disk electrode measurements. The catalysts exhibit high ORR activity in acidic (0.5 M H2 SO4 ) and alkaline (0.1 M KOH) electrolytes. A precursor structure−performance relationship of these catalysts and their performance trends in both electrolytes has been discussed in this work. Abstract : Code of conduct : The hydrothermal synthesis of Fe−N−C catalysts for high‐performance oxygen reduction in alkaline and acidic electrolytes is described. The hydrothermally derived catalysts are obtained from a glucose precursor and their structure−property relationship is evaluated by using physical and electrochemical characterization techniques. Analysis of the X‐ray diffraction data by the CarbonXS GUI code reveals the presence of face‐centered cubic iron nanoparticles in graphitic carbon lattices as the principle structure of the catalysts.